Githa Hariharan, When Dreams Travel (Picador, London, 1999, pp. 276. ISBN 0330372998) (Altre Modernità, 2009)
Githa Hariharan, When Dreams Travel(Picador, London, 1999, pp. 276. ISBN 0330372998)di Lorenza Dal Vera